2017
DOI: 10.3389/fpls.2017.02148
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Plasticity Is Important for Maintaining Sugarcane Growth under Water Deficit

Abstract: The water availability at early phenological stages is critical for crop establishment and sugarcane varieties show differential performance under drought. Herein, we evaluated the relative importance of morphological and physiological plasticity of young sugarcane plants grown under water deficit, testing the hypothesis that high phenotypic plasticity is associated with drought tolerance. IACSP95-5000 is a high yielding genotype and IACSP94-2094 has good performance under water limiting environments. Plants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 31 publications
2
25
1
Order By: Relevance
“…'IACSP97-4039' is the most indicated to restrictive environments with poor soils and water deficit (Gomes 2013). Marchiori et al (2017) verified that morphological and physiological traits are both cultivarand drought-dependent. Thus, it is important to understand cultivar response to different water deficit intensities.…”
Section: Experimental Design and Treatmentsmentioning
confidence: 74%
See 1 more Smart Citation
“…'IACSP97-4039' is the most indicated to restrictive environments with poor soils and water deficit (Gomes 2013). Marchiori et al (2017) verified that morphological and physiological traits are both cultivarand drought-dependent. Thus, it is important to understand cultivar response to different water deficit intensities.…”
Section: Experimental Design and Treatmentsmentioning
confidence: 74%
“…The secondary treatments (subplots) were the plastic trays containing one cultivar each: IAC91-1099, IACSP95-5000 and IACSP97-4039. 'IACSP95-5000' is recommended for fertile soils and some studies reported results that suggest it is susceptible to water deficit when compared to others (Machado et al 2009;Ribeiro et al 2013;Boaretto et al 2014), although Marchiori et al (2017) verified that it has some resistance to mild water stress. 'IAC91-1099' has higher plasticity than 'IACSP95-5000' concerning crop environment and it is suited for planting in regions with higher water deficit compared to 'IACSP95-5000' (Landell et al 2007).…”
Section: Experimental Design and Treatmentsmentioning
confidence: 99%
“…The physiological plasticity has a low cost and more rapid response with respect to the cost-expensive morphological plasticity, allowing the expression of the most adequate plant phenotype in response to the variable climatic conditions. For example, the plant physiological plasticity is strictly related to an enhanced ability to colonize gaps and open areas and, hence, exploiting the transient environmental resources at low cost by short-term adjustments, such as plant acclimatization [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. Conversely, the plant morphological plasticity is more functional for the plant adaptation in the long-term and probably useful for growing in forest understories [ 57 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study we sought to understand how the GB exogenous action occurs on the physiological mechanisms of tolerance to dehydration in young plants of sugarcane. This stage was chosen because it is considered to be the most susceptible to water deficiency, in addition to having the greatest changes in its metabolic activities and physiological plasticity in culture (Marchiori et al 2017;Endres et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, drought stress is one of the factors that most compromises sugarcane development and final yield, particularly in tropical regions (Jangpromma et al 2012;Silva et al 2013). Drought reduces primary growth and negatively interferes with physiological yield processes, such as gas exchange and photochemical efficiency of PSII (Sales et al 2013;Zivcak et al 2013;Marchiori et al 2017;Silva et al 2018).…”
Section: Introductionmentioning
confidence: 99%